MINI SEMINAR ENTREPRENEURSHIP to SMKN 1 STUDENTS BANDA ACEH - Mimiasri Mimiasri; Nasrul Hadi; M. Arief Setia Budi; Nuzulman Nuzulman (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2021)
The purpose of this service is to socialize and share knowledge about entrepreneurship for students at SMK Negeri 1 Banda Aceh so that they can foster enthusiasm and develop an entrepreneurial spirit that is smart to open an independent business after graduating from the learning process at school. The activities are aimed at students of SMK Negeri 1 Banda Aceh. The outputs obtained from this activity are (1) students gain motivation and knowledge in order to be able to open a business independently after graduating from the learning process. (2) From the results of the socialization, the students understood the content of the material and at the end of the session were given a question and answer time, some questions were obtained from students and the community.